An analysis of semiotic found in the selected skincare advertisement - Suwitri, Ni Luh Nita; Santika, I Dewa Ayu Devi Maharani; Pratiwi, Desak Putu Eka (Institut Pariwisata dan Bisnis Internasional, 2021)
Advertisement is a media that use to promote a product or service for the public. In the advertisement there are signs.. This study concern to analyze the verbal and non-verbal signs found in the skincare advertisement. There two aims of this study such as: (1) to find out the verbal and non-verbal signs in the skincare advertisement, (2) to analyze the meaning of verbal and non-verbal signs of the skincare advertisement. This study use descriptive qualitative method. The data were analyzed based on theory proposed by Barthes (1964) about the signifier and signified and about the meaning. The researcher used supporting theory by Wierzbicka (1996) about six color terms. The result of this study showed the verbal sign in form of written text and for the non-verbal sign showed in form of image. In this research the researcher found twenty (20) verbal signs and seven (7) non-verbal signs. And this sign also contains the denotative and connotative meaning